Contributions of islamic universities to professional ethics: a case study of International Islamic University, Malaysia and Crescent University, Abeokuta (2009)
This paper studies about the absence of moral and religious ethics in the formulation of professional ethics that is responsible for the Islamic ethical development. For this reason, this paper as a matter of urgency will in the remaining sections attempt to assess the teachings as it affects professional ethics, the contents and contexts of the syllabi and the curricular that make up the study of Islamic universities and the approaches adopted in teaching in order to demonstrate how Islamic Universities in particular impact on professional and moral ethics in the training of scientists, engineers, financial experts etc The teaching of Islamic ethics is today offered in Islamic universities like International Islamic University Malaysia and Crescent University, Abeokuta in Nigeria. This paper examines the objectives of teaching courses on Islamic ethics within the broader goals and objectives of the University system as well the Teaching Methodology employed in teaching these courses. In addition, it examines the overall academic context in which the courses are taught in these Islamic Universities.